2015
DOI: 10.1007/s11105-015-0872-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Associated to Drought Adaptation in Pea (Pisum sativum L.)

Abstract: Quantitative trait loci associated to drought tolerance in pea (Pisum sativum L.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…syriacum were used in this experiment to assess their proteomic response under water stress. These cultivars were selected based on previous screenings in which Kebby, Messire, and P665 were characterized as susceptible, moderately tolerant, and tolerant to water stress, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…syriacum were used in this experiment to assess their proteomic response under water stress. These cultivars were selected based on previous screenings in which Kebby, Messire, and P665 were characterized as susceptible, moderately tolerant, and tolerant to water stress, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Among legume crops, similar research has only been reported in cowpea (Lucas et al, 2013). However, advances have been made in mapping QTLs for resistance to abiotic stresses in pea, including for drought (Iglesias-Garcia et al, 2015), frost (Lejeune-Hénaut et al, 2008;Klein et al, 2014), and salinity (Leonforte et al, 2013). However, advances have been made in mapping QTLs for resistance to abiotic stresses in pea, including for drought (Iglesias-Garcia et al, 2015), frost (Lejeune-Hénaut et al, 2008;Klein et al, 2014), and salinity (Leonforte et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…These three (raffinose, stachyose, verbascose) are related in terms of their biosynthesis (Peterbauer et al, 2002 ). One of the enzymes involved (raffinose synthase, Rfs) shows genetic variation that maps approximately centrally on LG III (close to PSAB124, PSAA491 and PSAC18 markers in the JI 281 × JI 399 population; close to agpS1_SNP3 on LG III in Iglesias-García et al, 2015 ). The gene encoding a second enzyme of this pathway, stachyose synthase (Sts), has been mapped to LG V in another cross (cv.…”
Section: Resultsmentioning
confidence: 99%